2022
DOI: 10.1007/s00170-022-10204-4
|View full text |Cite|
|
Sign up to set email alerts
|

A phase-field study of neck growth in electron beam powder bed fusion (EB-PBF) process of Ti6Al4V powders under different processing conditions

Abstract: Traditional sintering processes are carried out to achieve complete material densification. In an electron beam powder bed fusion (EB-PBF) process, the same sintering mechanisms occur but only with the aim to form small connections between the particles (necks). A proper neck formation is central for the EB-PBF process because, among other effects, ensures the thermal stability of the process and helps to avoid smoke phenomena. This work presents a numerical study of neck formation under the EB-PBF processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 88 publications
0
0
0
Order By: Relevance
“…Experimental comparisons indicate that the phase-field model incorporating temperature field evolution accurately predicts the distribution of temperature fields and variations in microstructural morphology during selective laser sintering. Rizza et al [90] simulated the morphological changes in electron beam-melted Ti6Al4V powder under different temperature histories. They found that both temperature history and powder geometry influence the sintering rate and neck size.…”
Section: Phase-field Sintering Model With Temperature Fieldmentioning
confidence: 99%
“…Experimental comparisons indicate that the phase-field model incorporating temperature field evolution accurately predicts the distribution of temperature fields and variations in microstructural morphology during selective laser sintering. Rizza et al [90] simulated the morphological changes in electron beam-melted Ti6Al4V powder under different temperature histories. They found that both temperature history and powder geometry influence the sintering rate and neck size.…”
Section: Phase-field Sintering Model With Temperature Fieldmentioning
confidence: 99%